The Moderating Role of Corporate Governance in the Relationship Between XBRL Adoption and Information Asymmetry: Evidence from Indonesian Technology Firms - Anak Agung Putu Gede Bagus Arie Susandya; Ni Nyoman Ayu Suryandari (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines the effect of Extensible Business Reporting Language (XBRL)-based financial reporting on information asymmetry and investigates whether corporate governance moderates this relationship. Although XBRL is widely promoted as a digital reporting mechanism that improves accessibility, comparability, and transparency, its effectiveness in emerging markets remains inconclusive. This study focuses on technology sector companies listed on the Indonesia Stock Exchange during 2020–2022. Using 63 firm-year observations from 21 companies, data were collected from annual reports, financial statements, stock trading data, and other public corporate information. The data were analyzed using moderated regression analysis. Contrary to the initial expectation, the findings show that XBRL adoption has a positive and significant effect on information asymmetry, measured by bid-ask spread. This indicates that XBRL adoption does not automatically reduce information asymmetry in Indonesian technology firms. The interaction between XBRL adoption and corporate governance is also positive and significant, suggesting that corporate governance strengthens the positive association between XBRL adoption and information asymmetry. These findings imply that digital reporting technology alone is insufficient to improve transparency without adequate investor capability, reporting quality, governance substance, and institutional enforcement.